[Translated article] Superior capsular reconstruction of the shoulder with biceps autograft vs. Achilles allograft: A 2-year comparative study - D.J. Gómez; S. Ávila Posada; N. Gabotto; G.M. Viollaz; Á.J. Muratore; N.N. Altamirano; D. Moya (Revista Española de Cirugía Ortopédica y Traumatología)
Purpose: To retrospectively evaluate the clinical–functional outcomes, healing rates, complications, and surgical time in patients treated with superior capsular reconstruction (SCR) using long head of the biceps autograft (LHB) and Achilles allograft (AA). Materials and methods: This retrospective study included 24 patients with irreparable rotator cuff tears of the supraspinatus and infraspinatus, treated with SCR. Two treatment groups were formed: one with 12 cases using AA and another with 12 cases using LHB. All patients were followed for a minimum of 2 years. Results: The SSV was 73.7 ± 25.3 vs. 86.0 ± 8.7 (p = 0.26), the Constant score was 76.8 ± 20.1 vs. 83.7 ± 4.6 (p = 0.12), and the VAS was 1.6 ± 2.3 vs. 1.7 ± 0.5 (p = 0.9) for the LHB and AA groups, respectively. Tendon healing was 66.7% in AA and 100% in LHB (p = 0.001). Complications were 50% in AA and 0% in LHB. The average surgical time was 127.7 ± 37.6 min for AA and 84.3 ± 14.3 min for LHB (p = 0.01). Conclusions: SCR with LHB showed better results in terms of tendon healing, fewer complications, and reduced surgical time compared to the use of AA. Resumen: Propósito: Evaluar retrospectivamente los resultados clínico-funcionales, las tasas de cicatrización, las complicaciones y el tiempo quirúrgico en pacientes tratados con reconstrucción capsular superior (RCS) usando autoinjerto de porción larga de bíceps (PLB) y aloinjerto de Aquiles (AA). Materiales y métodos: Estudio retrospectivo que incluyó 24 pacientes con roturas irreparables del supraespinoso e infraespinoso tratados con RCS. Se conformaron 2 grupos de tratamiento: uno con 12 casos utilizando AA y otro con 12 casos utilizando PLB. Todos los pacientes fueron seguidos durante un mínimo de 2 años. Resultados: El SSV fue de 73,7 ± 25,3 vs. 86,0 ± 8,7 (p = 0,26), la escala de Constant fue de 76,8 ± 20,1 vs. 83,7 ± 4,6 (p = 0,12) y la EVA de 1,6 ± 2,3 vs. 1,7 ± 0,5 (p = 0,9) para los grupos PLB y AA, respectivamente. La cicatrización tendinosa fue del 66,7% en AA y del 100% en PLB (p = 0,001). Las complicaciones fueron del 50% en AA y del 0% en PLB. El tiempo quirúrgico promedio fue de 127,7 ± 37,6 minutos para AA y 84,3 ± 14,3 minutos para PLB (p = 0,01). Conclusiones: La RCS con PLB ha mostrado mejores resultados en términos de cicatrización tendinosa, menos complicaciones y un tiempo quirúrgico reducido al compararlo con la utilización de AA.